2014
DOI: 10.1007/s11095-014-1482-4
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Kinase Gene Delivery Using Curcumin Loaded Peptide Micelles as a Combination Therapy for Glioblastoma

Abstract: R7L10 is an efficient carrier for delivery of curcumin and the HSVtk gene, which may be a useful combination therapy for glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In the previous study, R7L10 was evaluated as a gene carrier for the lung . R7L10 was also evaluated as a gene carrier for tumor animal models . Therefore, the first purpose of the current study was to confirm that R7L10 delivered pEpo–NI2–SV–HSVtk into the tumor and elicited the therapeutic effects.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the previous study, R7L10 was evaluated as a gene carrier for the lung . R7L10 was also evaluated as a gene carrier for tumor animal models . Therefore, the first purpose of the current study was to confirm that R7L10 delivered pEpo–NI2–SV–HSVtk into the tumor and elicited the therapeutic effects.…”
Section: Discussionmentioning
confidence: 89%
“…12 R7L10 was also evaluated as a gene carrier for tumor animal models. 33 Therefore, the first purpose of the current study was to confirm that R7L10 delivered pEpo-NI2-SV-HSVtk into the tumor and elicited the therapeutic effects. In Figure 7, the pEpo-NI2-SV-HSVtk/R7L10 complexes inhibited the tumor growth at all tested doses.…”
Section: Discussionmentioning
confidence: 90%
“…Our previous study showed that HSV-TK/GCV treatment induced cell apoptosis and inhibited tumor growth (Xiao et al 2018). By loading curcumin into the P7L10 peptide micelles to be a more efficient carrier for HSV-TK gene delivery, Park et al reported that HSV-tk/R7L10-Cur complex induced C6 rat glioblastoma cell death and reduced the tumor size of xenografted glioblastoma (Park et al 2015). However, the mechanism was not studied and the dose of curcumin was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The in-vivo results showed that R7L10-curcumin delivered pDNA with better efficiency and reduced the TNF-a level in lung tissues in an acute lung injury mouse model [166]. Similarly, to assess the effect of combination therapy, CUR was delivered along with herpes simplex virus thymidine kinase (HSVtk) gene using R7L10 peptide micelles as a carrier in glioblastoma animal model [167]. CUR was found to deliver more efficiently into cells by R7L10-CUR micelles than CUR alone.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…CUR was found to deliver more efficiently into cells by R7L10-CUR micelles than CUR alone. R7L10-CUR micelles induced cell death efficiently in in-vitro as well as in-vivo study [167]. Recently, Martin et al [168] accounted simultaneous loading of lipophilic gold nanorods (GNRs) and CUR into polymeric nanomicelles prepared from biocompatible PLGA-b-PEG copolymer for efficient in-vivo photothermal therapy of Barrett Esophagus.…”
Section: Polymeric Micellesmentioning
confidence: 99%